Analisis Penggunaan Prinsip Akuntansi Manajemen pada UMKM Aceh Barat - Fitria Mandaraira (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2023)
This study aims to identify the behavior of the Micro, Small, and Medium enterprise within West Aceh in managing financial and operational activities of the business. The object of the research was randomly selected of 30 micro, small and medium enterprises located in West Aceh. The method of the study is a qualitative method with analysis descriptive approach using interview, observation and questionnaire as the technic of data collection. The result of the study shows that the practice of management accounting of the business is not compatible with the actual principle of the concept. Some respondents believe that their businesses operate normally as in fact they are not developing. Others consider that the development of technology and information are not relevant in increasing business’ performance and feasibility. Keywords: Management Accounting, SMEs